(untitled) (American Journal of Islam and Society, 2003)
Wholeness and Holiness in Education: An Islamic Perspective is a very interesting book. Although the book is a result of her experience as a Muslim graduate student in Canada, she does not mention any personal reasons for writing this book, but rather tackles it very lightly without mentioning the hard experiences she faced when her faith was questioned. A Muslim who has taken her faith for granted for years and had had little or no communication with the West was questioned for the first time in her life about many aspects of her faith and found herself unable to provide adequate answers. Her book is the result of such an experience, one which many others in her circumstances and situation have faced and will have to face. Although the author frequently tackles abstract ideas, she always provides scholarly explanations and discussions by quoting and elaborating upon many well-known figures in various disciplines. The book is divided into four parts and has a total of nine chapters. The first part, “Reflection on Personal Experience,” includes two chapters. In them, she tries to take the reader from her own personal experience to the book’s goal: preparing Muslim students in their homelands’ educational systems to think and question their faith so that they can stand on solid ground. In chapter 1, “The Spiritual and Intellectual Journey,” she apologizes for including her personal experience growing up as a Muslim. Actually, more elaboration upon such experiences and on the conflicts she faced while studying in Canada would have been appreciated, as such a topic requires that personal experiences be shared, given that they are not limited to one person but rather to millions of individuals. Chapter 2, “Spirituality: Woman’s Best-Kept Secret,” further analyzes the significance of such experiences to women specifically ...